Evaluation: The First Step in Training Cycle - Balogun, Akinyemi (Journal of Economics and Behavioral Studies, 2011)
If organizations (Financial Institution inclusive) intensify and invest a lot on the training of their personnel, this study contends that evaluation, â€œIntegral Part of Training should be senses the â€œFirst Stepâ€ by Trainers in Training Cycle. The basic objective in evaluation is to assess the effectiveness of a training aid, a kind of feedback by which the trainer is informed about the areas of strength and weakness in the programme and most importantly is the question of investment and commitment to training on the part of government. Evaluation is simply the obtaining of selective information about the effects of training. The valve of such information is determined by the use to which it is put. If Evaluation is properly taken care of a more professional approach to training will mean that trainers will not be regarded as trainers unless among other things, they are themselves technically conversant with the methods and techniques of the evaluation of training. The knowledge and the resources committed to training will not then be seen as a waste but as an integral part of training, to deliver a training programme without evaluation is like standing on one foot.